Assessing the gaps in knowledge of female health workers about monthly HMIS reports and its utilisation - Mahajan, Shuchi; Aggarwal, Arun K. (International Journal Of Community Medicine And Public Health, 2021)
Background: Health management information system (HMIS) aims to gather, aggregate, analyse and then use the information to take actions for improvement in the performance of the health systems. This study documents the knowledge of FHWs to the monthly reports that they need to prepare and submit for HMIS. Objective was to assess the knowledge of FHWs with respect to utilisation, understanding and feedback from supervisor for monthly reports Methods: The cross sectional study was conducted in the RaipurRani block, District Panchkula of Haryana. The assessment of FHWs was done as per semi structured questionnaire which was restricted to the monthly reports that they need to prepare and submit. FHWs of selected facilities that were available and gave consent were interviewed. Results: Out of 9 FHWs, 5 had undergone training to fill the single line proforma. Seven of them said that their reports got checked and they got regular feedback. Three said that they get motivated by senior officials but 5 said that there is no motivating factor. Two said that they got demotivated by the rude behaviour and scoldings of the senior officials. All the FHWs said that it is useful to prepare the reports. With respect to timeliness of reports, in this study we found that all the reports were sent on time within deadline. Conclusions: Despite of such low motivation on use of HMIS, the majority of the FHWs had positive attitude towards the system, indicating substantial acceptability, a positive potential factor for improvement.